IIB matrix model and regularized big bang. (21st May 2021) - Klinkhamer, F R
Abstract: The large- N master field of the Lorentzian IIB matrix model can, in principle, give rise to a particular degenerate metric relevant to a regularized big bang. The length parameter of this degenerate metric is then calculated in terms of the IIB-matrix-model length scale.